Specifying WHO recommendation: moving toward disease-specific guidelines. - Gaertner, Jan; Wolf, Juergen; Ostgathe, Christoph; Toepelt, Karin; Glossmann, Jan Peter; Hallek, Michael; Voltz, Raymond (Journal of palliative medicine, 2010)
INTRODUCTION: The World Health Organization (WHO) explicitly recommends the integration of palliative care (PC) early in the disease trajectory as part of the WHO definition of PC. Our comprehensive cancer center decided: (1) to include this recommendation in the administrative directives for principles of cancer care and (2) to establish a PC hospital support team. The evaluation of this approach revealed that patients with lung cancer still received PC rather late in the course of the disease. Therefore, we decided to additionally develop disease-specific standard operating procedures (SOPs) to try to overcome these deficiencies. The first SOP was completed for patients with lung cancer. STANDARD OPERATING PROCEDURE (Consensus SOP): Specifically, the SOP states that: "Specialized PC is recommended regularly for all lung cancer patients without curative treatment options, specifically patients with (i) metastasized and inoperable or (ii) locally advanced and inoperable or (iii) relapsing lung cancer. Integration of PC is recommended simultaneously to starting tumor-specific therapy. In this context, initial PC should be delivered to the patient at the same place as specific treatment, which is the interdisciplinary outpatient unit of the Center of Integrated Oncology (CIO) or an oncological ward." DISCUSSION: This SOP for the first time presents disease-specific guidelines for PC integration into comprehensive (lung) cancer therapy by (1) defining "green flags" for early integration of PC and (2) recommending PC parallel to initiation of anticancer therapy. Furthermore, clear definitions are provided to delineate PC assignments. Such disease-specific algorithms should be helpful to further reduce uncertainty about the way PC can be integrated early in the course of the disease.
CRIS-Team Scopus Importer:2025-10-27